Reduction of Particulate Matter Emission from Four-Stroke Marine Diesel Engine by Electrostatic Cyclone DPF (Analysis of Particulate Size Distribution) - ZHU, Hongrun; SASAKI, Hidetsugu; FURUGEN, Munekatsu; TSUKAMOTO, Tatsuro; MAKINO, Tadashi (Nihon Kikai Gakkai rombunshuu. B hen, 2011)
In this paper, an Electrostatic-Cyclone DPF (Diesel Particulate Filer) has been developed to reduce the Particulate Matter (PM) from a marine diesel engine. Size distribution of the PM in the exhaust gas of four-stroke marine engine (1200rpm, 67.3kw) was measured by a Scanning Mobility Particle Sizer (SMPS) and a Low Pressure Impactor (LPI). The experimental results demonstrate that particles of less than 1 μm in diameter account for a major portion of the PM and that the DPF can collect fine particles in the PM (not exceed 500nm in diameter) from the engine exhaust gas. The DPF shows high collection efficiency for particles under 200 nm in diameter.